(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
قمنا في هذا البحث بدراسة العمر ومعدلات النمو لأسماك البوري شيلان في المياه البحرية لمدينة اللاذقية، حيث جمعت عينات عشوائية خلال العام 2008م بمعدل مرتين شهرياً باستخدام شباك إحاطة ساحلية بقطر فتحات 20ملم. بينت نتائج دراسة العلاقة بين الطول والوزن, أن النمو عند أفراد النوع السمكي المدروس هو من النمط growth (b<3) Allometric, مع عدم وجود فروقات معنوية بين الذكور والاناث P>0.05)). كما أظهرت نتائج الدراسة أن معدلات النمو في الطول والوزن عند الذكور(36.61% للطول- 40.24% للوزن) كانت أعلى منها عند الإناث 30.96%) للطول- 25.24% للوزن), في حين كان معدل النفوق الطبيعي (M) عند الإناث أعلى منه عند الذكور(0.34 و0.23 على التوالي). حددت في هذه الدراسة أيضاً ثوابت معاملات النمو النظرية تبعاً لمعادلات Von- Bertalanffy لكل من الذكور (L∞=73.14cm, K=0.15, t∞=-0.387& W∞=3227g) والاناث (L∞=56cm, K=0.22, t0= 0.240 & W∞=1575g- ) والعينة الإجمالية (L∞=61.25cm, K=0.17, t0=-0.312 & W∞=2119g.). The aim of this paper was to study the age and growth of chelon labrosus, in the marine waters of Lattakia. So, monthly random samples were taken during 2008 by coastal trammels with 20 mm mesh size..The length-weight relationship results showed an Allometric Growth type in the studied species (b<3), with no significance between males and females (P>0.05). Our results showed that the length and weight rates of males (36.61% for length-40.24% for weight) were higher than females (30.96% for length- 25.24% for weight), whereas the natural mortality (M) of females was higher than males (0.34 &0.23, respectively). Von–Bertalanffy growth (theoretical growth) parameters were estimated, for males (L∞=73.14cm,K=0.15,t0=-0.387& W∞=3227g.),females (L∞=56 cm, K=o.22,t0=-0.240 & W∞=1575g.) and all samples (L∞=61.25cm, K=0.17, t0=-0.312& W∞=2119g.).